Abc is an isosceles triangle with ab equals to ac and also given that ec equals to bd prove that ae equals ad
Answers
Answered by
2
given ab=ac
ec=bd
by cpct the triangle ABC and DEF
so this is prove that ae =ad
ec=bd
by cpct the triangle ABC and DEF
so this is prove that ae =ad
Answered by
2
AB=AC (given)
angle A= angleA [common
and
angle E= angle D { each 90°}
therefore by AAS rule ∆ AEC ≈ ∆ ADB
BY CPCT
AD=AE
angle A= angleA [common
and
angle E= angle D { each 90°}
therefore by AAS rule ∆ AEC ≈ ∆ ADB
BY CPCT
AD=AE
Similar questions